Corporate Social Responsibility among the Small and Medium Sized Enterprises in Kazakhstan - Aizhan, Zhaimina (2014)
This research has been executed in order to find out the role of corporate social responsibility among the small and medium sized enterprises in Kazakhstan. To achieve the set aim to research, some objectives have been set. One of the objectives of this research is to find out the role of CSR in the development of the business. Hence, in this regard the findings of this research conclude that, in the current era CSR plays a crucial role in the development of the business, because when the stakeholders of the organizations know that, the company is not only functioning in the industry to make profits, but is also making to provide benefits to its stakeholders, this results in enhancing the overall performance of the business. The results of this research related to the last factor of CSR i.e. philanthropic responsibility, it is concluded that, philanthropic responsibility does not significantly impacts the performance of SMEs in Kazakhstan. Move over, the findings of this research also highlight that, there is no relationship between philanthropic responsibility and performance of SMEs in Kazakhstan. However, the managers of SMEs, who have been a part of the survey of this research illustrates that, this responsibility mainly covers those practices and activities that are highly desirable for every individual of the society. On the whole, the findings of this research conclude that, CSR is one of the important parts of the business operations and implementation of CSR activities, especially related to ethical, legal and economic responsibility is crucial to enhance the performance of small and medium sized enterprises in Kazakhstan.